Evaluating and supporting the intercultural capabilities of pharmacy undergraduates - Bridges, S.J. (2014)
The thesis takes a human development approach to the potential value of international higher education. It evaluates the intercultural capabilities of UK and international pharmacy students in one university. As graduates and professional pharmacists these students will serve a diverse population of patients and work in multi-professional, multi-skilled and multi-cultural teams. Despite internationalised higher education offering a multicultural space in which students could forge a more global outlook, the reality found was that the potential is not realised in the case of many students.